Hubungan Diplomatik Indonesia-Brunei Darussalam Pada Masa Presiden Suharto & Sultan Hassanal Bolkiah, 1984-1998 - Ahmad Musyalen Firdaus; Nurzengky Ibrahim; Kurniawati Kurniawati (Universitas Hamzanwadi, 2023)
This research aims to explain how Indonesia's Diplomatic Relations with Brunei Darussalam developed in the 1984-1998 period. The research method used is a historical method consisting of heuristics, source criticism or verification, interpretation and historiography. In collecting sources, the author uses sources from contemporary newspapers and source books related to the discussion. The results of this research are that Indonesia and Brunei Darussalam have had good relations since the time of the kingdoms in the archipelago. One proof of this good relationship is the kinship between the Brunei Royal family and the Majapahit Kingdom. During the Guided Democracy era, Indonesia and Brunei had cold relations due to differences in political views between President Sukarno and the Sultan of Brunei Sir Omar Ali Saifuddin III regarding the movement for the Unitary State of North Kalimantan led by A.M. Azahari. During President Suharto's time, Indonesia restarted diplomatic relations with Brunei Darussalam which began in 1981 until official diplomatic relations in January 1984. In its development until May 1998, Indonesia's diplomatic relations with Brunei Darussalam went well with a high spirit of friendship. This can be seen through various collaborations in various fields such as politics, economics, education and tourism. The political and economic fields are the most impressive areas in diplomatic relations between the two countries. One of them is that Brunei Darussalam provided an interest-free loan to Indonesia in 1987.